The Effect of Self-Efficacy, Field Work Practices and Motivation to Enter The World of Work on Accounting Vocational School Students' Work Readiness in Nunukan Regency - Endriyan Sumaili; Maimun Maimun (Global Economics: International Journal of Economic, Social and Development Sciences, 2025)
This study aims to determine the effect of self-efficacy, field work practice and motivation to enter the world of work on the work readiness of students of Accounting Vocational School, Nunukan Regency. This study uses a descriptive verification research design with a survey approach that has been implemented at the Accounting Vocational School of Nunukan Regency. The subjects in this study were students of class XII Accounting in 3 vocational schools in Nunukan Regency, namely SMKN 1 Nunukan, SMKN 1 Sebatik Barat and SMKN 1 Tulin Onsoi, consisting of 100 female students and 37 male students. The objects of this study are self-efficacy, field work practices, motivation to enter the world of work and work readiness of vocational school students. The data collected through the questionnaire were then processed/analyzed. To test the hypothesis using multiple linear regression. The results of the study indicate that there is a positive and significant influence of self-efficacy, field work practice and motivation to enter the world of work on the work readiness of students of Accounting Vocational High Schools in Nunukan Regency, which is indicated by the results of the multiple linear regression test obtained a multiple correlation coefficient of 0.618 which is included in the category of a strong relationship level with a determination level of 0.382 or in other words, the work readiness variable of vocational high school students is influenced by self-efficacy, field work practice and motivation to enter the world of work by 38.2% with Fcount> Ftable or 26.691> 3.940, then H0 is rejected and accepts H1 which states that there is an influence of self-efficacy, field work practice and motivation to enter the world of work on the work readiness of students of Accounting Vocational High Schools throughout Nunukan Regency.